Effect of food value-chain connections on land-use change - P.M. Post; Y. Dou; A. Nelson (Geography and Sustainability)
Changes in food production, often driven by distant demand, have a significant influence on sustainable management and use of land and water, and are in turn a driving factor of biodiversity change. While the connection between land use and demand through value chains is increasingly understood, there is no comprehensive conceptualisation of this relationship. To address this gap, we propose a conceptual framework and use it as a basis for a systematic review to characterise value-chain connection and explore its influence on land-use and -cover change. Our search in June 2022 on Web of Science and Scopus yielded 198 documents, describing studies completed after the year 2000 that provide information on both value-chain connection and land-use or -cover change. In total, we used 531 distinct cases to assess how frequently particular types of land-use or -cover change and value-chain connections co-occurred, and synthesized findings on their relations. Our findings confirm that 1) market integration is associated with intensification; 2) land managers with environmental standards more frequently adopt environmentally friendly practices; 3) physical and value-chain distances to consumers play a crucial role, with shorter distances associated with environmentally friendly practices and global chains linked to intensification and expansion. Incorporating these characteristics in existing theories of land-system change, would significantly advance understanding of land managers’ decision-making, ultimately guiding more environmentally responsible production systems and contributing to global sustainability goals.